Pushing the Envelope: Skin-Only Mastopexy in Single-Stage Nipple-Sparing Mastectomy with Direct-to-Implant Breast Reconstruction. Issue 1 (24th December 2020) - Aliotta, Rachel E.; Scomacao, Isis; Duraes, Eliana F. R.; Kwiecien, Grzegorz J.; Durand, Paul D.; Fanning, Alicia; Moreira, Andrea
Abstract : Background: Despite advances in skin envelope reduction techniques and experienced nipple-sparing mastectomy flap procedures, the rate of nipple malposition and secondary revision in these patients remains high and eligible candidates are limited. In this article, the authors present a novel technique combining skin reduction nipple-sparing mastectomy surgery with single-stage skin-only mastopexy and direct-to-implant reconstruction. Methods: A retrospective review was performed at a single institution from 2015 to 2018. All patients were operated on using this technique consecutively, by a breast and plastic surgeon team (A.F. and A.M.). Surgical technique and outcomes were compared with the currently accepted literature. Results: Twenty-six patients (40 breasts) underwent this technique; all were single-stage direct-to-implant reconstructions. The average body mass index was 31 kg/m 2 . A Wise pattern was used in 35 breasts (87.5 percent) and prepectoral placement was used in 25 breasts (62.5 percent). Overall complications included seroma [ n = 6 (15 percent)], vertical/T-junction dehiscence [ n = 4 (10 percent)], skin necrosis [ n = 4 (10 percent)], superficial or partial nipple necrosis [ n = 4 (10 percent)], with no total nipple-areola complex lost and no reconstructive failures at 18.7 months' average follow-up. Conclusions: In this article, the authors share a novel reconstructive technique in which the skin envelope is reduced, the nipple-areola complex is repositioned, and a direct-to-implant reconstruction is performed in a single stage at the time of mastectomy. Consideration of pearls and pitfalls accompanies a review of the authors' experienced complication profile, and is discussed in the context of current literature. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.